THE USE OF PAIR WORK TO REDUCE SPEAKING ANXIETY IN AN EFL CLASSROOM - Mutiara Putri Aulia, - (2019)
Anxiety in speaking is one of the common obstacles in learning English as a foreign language. To help students in reducing speaking anxiety, teachers need to find a suitable teaching strategy. Based on the issue, this study is aimed to find out the level of speaking anxiety among EFL students and investigate the use of pair work as a teaching strategy in reducing students' speaking anxiety in an EFL Classroom. The research method used in this study was qualitative method in form of teacher as a researcher. The data were collected by using three instruments; questionnaire, observation and interview. Based on the questionnaire, there are five categories in measuring the level of speaking anxiety which are "very relaxed", "relaxed", "mildly anxious", "anxious" and "very anxious". From 31 students, it was found that only one student who was categorized as a very relaxed student and two students were classified as relaxed. These three students were chosen to be the less anxious students. Meanwhile, there were 10 students who were categorized into mildly anxious and 11 anxious students. Lastly, seven "very anxious" students were identified in the classroom. In this study, the less anxious students were paired with three anxious students from different level (mildly anxious, anxious and very anxious). As a result, pair work successfully lessened students' speaking anxiety by providing five characteristics among students' activity especially in promoting interaction between students and the opportunity to speak where the less anxious student help the anxious students in pronouncing certain words and inform the suitable vocabularies. Kecemasan dalam berbicara adalah salah satu dari hambatan-hambatan yang umum terjadi dalam pembelajaran bahasa Inggris sebagai bahasa asing. Untuk membantu siswa dalam mengurangi kecemasan berbicara, guru harus menemukan strategi pengajaran yang sesuai. Berdasarkan masalah tersebut, penelitian ini bertujuan untuk mengetahui tingkat kecemasan berbicara di antara siswa bahasa Inggris dan meneliti penggunaan teknik berpasangan (pair work) sebagai strategi mengajar dalam mengurangi kecemasan berbicara yang dialami siswa dalam kelas bahasa Inggris. Metode penelitian yang digunakan dalam penelitian ini adalah metode kualitatif dalam bentuk guru sebagai peneliti. Teknik pengumpulan data dengan menggunakan tiga instrumen yaitu kuesioner, obervasi dan wawancara. Berdasarkan kuesioner, terdapat lima kategori dalam mengukur tingkat kecemasan berbicara yaitu "sangat rileks", "rileks", "sedikit cemas", "cemas" dan "sangat cemas". Dari 31 siswa, ditemukan hanya satu siswa yang masuk dalam kategori "sangat rileks" dan dua siswa tergolong "rileks". Ketiga siswa ini dipilih sebagai siswa yang tidak cemas. Sementara itu, 10 siswa masuk ke dalam kategori "sedikit cemas" dan terdapat 11 siswa yang "cemas". Terakhir, 7 siswa dengan kategori "sangat cemas". Dalam penelitian ini, siswa yang tidak cemas dipasangkan dengan siswa yang cemas yang berasal dari tingkatan yang berbeda (sedikit cemas, cemas dan sangat cemas). Penelitian ini menemukan bahwa pair work berhasil mengurangi kecemasan berbicara pada siswa melalui lima karakteristik dalam kegiatan siswa khususnya dalam meningkatkan interaksi antar siswa dan kesempatan berbicara dimana siswa yang tidak cemas membantu siswa yang cemas dalam mengucapkan kata-kata tertentu dan memberitahu kosa kata yang tepat.